(3GdeONd GdeajO hZfjI GdeSJajO aj GdMce Ydi GdehGdjOs - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj , GHf CHj GdoqTrcQ , J fMh (B680 (3g`s ((3YHO GdQRGb Hf eMeO GdedbH HeYjf GdefLe GdcSGTi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GHOY GdhLhO bGd ehdGfG bO LeYJ ai gPG GdcJGH fHOkG ef GbGhjd GdMceGA GdaUd GdChd ai PcQ GdHQhL s
(3BNQgG (B:s
(3hai GdMGOi YTQ jMQe NjQ dGUObGFI hjQLYhf Edi eYGOGJg hjchf TbjkG hajeG PcQfG caGjI afNJe GdcJGH HgPG GdHGH s
(3HChdg JedcGJ HgG fXGe GdJYbjHIs
(3HBNQgG LOGhds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(2440) s
Keywords: (3Gdadcs